Anger, ventricular arrhythmias and sudden death. (VITAE Academia Biomédica Digital, 2002)
Recent studies provide clear and convincing evidence that anger contributes significantly to the pathogenesis and expression of coronary artery disease. Several investigations have linked anger attribute to several aspects of coronary artery disease including: 1. - Association with coronary risk factors (lipid levels, cardiovascular reactivity and blood pressure) 2. - Coronary disease pathogenesis, morbidity and mortality 3. - Triggering of acute coronary syndromes 4. - Progression of coronary atherosclerosis induced by anger 5. - Ventricular arrhythmias and sudden death. Evidence from prospective epidemiological and clinical studies, supported by experimental studies lend to a casual association between anger and ventricular arrhythmia and sudden cardiac death.